2017
DOI: 10.1007/s10549-017-4385-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase 4/6 inhibitors in breast cancer: palbociclib, ribociclib, and abemaciclib

Abstract: After having demonstrated impressive activity in ER-positive, HER2-negative metastatic breast cancer, currently CDK4/6 inhibitors are in further development. It is obvious that this class of agents with their efficacy, low and easily manageable toxicity, and oral dosage is a very important treatment option for breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
125
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(132 citation statements)
references
References 59 publications
0
125
0
2
Order By: Relevance
“…A previous study reported that dysregulation of the CDK4‐RB pathway is an important contributor to endocrine therapy resistance . To test this, we established the tamoxifen‐resistant MCF7/TR cell line through long‐term culture of ER‐positive MCF7 cells with increasing concentrations of tamoxifen.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that dysregulation of the CDK4‐RB pathway is an important contributor to endocrine therapy resistance . To test this, we established the tamoxifen‐resistant MCF7/TR cell line through long‐term culture of ER‐positive MCF7 cells with increasing concentrations of tamoxifen.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclin‐dependent kinase 6 (Cdk6), as a catalytic subunit of protein kinase complex, is involved in the regulation of cell cycle . The inhibitors of Cdk6 were shown to be a promising agents in the treatment of various tumors via suppressing G1/S phases progression of the cell cycle. Cdk inhibition also upregulated immediate senescence of small cell lung cancer cell, and Cdk4/6 inhibitors were found to be effective on treatment of NSCLC .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in vivo study showed that trastuzumab combined with abemaciclib inhibited tumor growth more than either single agent (84). In another preclinical study, abemaciclib with trastuzumab significantly improved tumor growth inhibition and tumor regressions in xenografts progressing on trastuzumab alone (81). In a phase I study, one patient with hormone receptor-negative and HER2…”
Section: Her2 Tk Inhibitorsmentioning
confidence: 98%
“…CDK4/6 inhibitors have shown great potential in preclinical studies and clinical trials, such as palbocilcib and ribociclib which has been applied in clinical (79,80). Though CDK4/6 inhibitors are mainly used to treat estrogen receptor (ER) + /HER2 -patients, some studies found that they also have potential therapeutic effect on ER + /HER2 + patients (81). In an exploratory, open-label, phase 2 study (NA-PHER2), the combination of palbociclib, fulvestrant, trastuzumab and pertuzumab was found reduced the expression of Ki67 significantly (82).…”
Section: Her2 Tk Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation